(untitled) (Yangi O’zbekiston taraqqiyotida tadqiqotlarni o’rni va rivojlanish omillari, 2024)
This article provides information about the challenges and advantages that a teacher may face when teaching English as a second language. Learning foreign languages ​​is neither easy nor very difficult, but teaching them has a number of complexities and can be difficult for any teacher except for qualified and experienced teachers. Teachers who learn English once and then teach this language, no matter what difficulties they encounter, their knowledge will continue to grow.